The Effect of Clinical Ambiguity on the Decision-Making Process Among Intensive Care Unit Providers in Northern America Using Clinical Vignettes in Mixed Methods Study - Fleck D; Gad H; Hogan Quigley B; Antar M; Sayed Ahmed A; Mahmoud MA; Laudanski K (Journal of Multidisciplinary Healthcare, 2025)
Desiree Fleck,1,* Hossam Gad,2,* Beth Hogan Quigley,1,* Mohamed Antar,2 Ahmed Sayed Ahmed,3 Mohamed A Mahmoud,3 Krzysztof Laudanski2 1Department of Nursing, University of Pennsylvania, Philadelphia, PA, USA; 2Department of Anesthesiology and Perioperative Care, Mayo Clinic, Rochester, MN, USA; 3Pulmonary and Critical Care Division, Mayo Clinic, Rochester, MN, USA*These authors contributed equally to this workCorrespondence: Krzysztof Laudanski, Department of Anesthesiology and Perioperative Care, Mayo Clinic, 200 1st St Rochester, Rochester, MN, 55902, USA, Tel +1508-762-9587, Email laudanski.krzysztof@mayo.eduPurpose: Our study investigates how healthcare professionals in the Intensive Care Unit make decisions under highly ambiguous conditions, where the patient’s presentation triggers initial protocolized treatment but subsequently fails to respond to medical treatment. We hypothesize that providers with a low tolerance for ambiguity and specific risk-taking preferences are likely to rapidly engage in adequate evidence-based strategies when dealing with high-risk illnesses such as sepsis.Patients and Methods: This is a single-center cohort mixed method study of healthcare providers (attendings, fellows, residents, and advanced care providers) (n=138) using clinical vignettes (Vignette#1 representing the case of sepsis, Vignette#2 representing an ambiguous case). Participants were recruited using an internal Email distribution list (response rate 13.63%). Providers were asked to choose any number of specific therapies while being assessed for tolerance of ambiguity, denial mechanism, anxiety, prevalence of risk-taking behavior, optimism, and decision-making style.Results: Providers sparsely used antibiotics in vignette #2, while fluids were rarely given in vignette #1 during the first 48 hours. By day three, providers had implemented mechanical ventilation and renal replacement therapies. Bicarbonate and corticosteroids were used significantly as collateral therapies. Study participants were not very tolerant of ambiguity, used defensive mechanisms, and more often used rational decision-making rather than intuitive decision-making. Healthcare experience correlated negatively with the stress of uncertainty, defensiveness, and rational thinking. Optimism correlated positively with years of healthcare experience. The percentage of intensive care unit responsibilities correlated with risk-taking behaviors and defensiveness. There was no difference between implementers of the bundle and never implementers in their demographic, professional, and psychological characteristics. A similar lack of correlation was seen between different levels of tolerance of ambiguity among providers.Conclusion: Providers’ experience working in the intensive care unit, combined with their level of optimism, seemed to influence the relatively low implementation of the sepsis bundle across two vignettes.Keywords: clinical decision-making, sepsis management, risk-taking behavior, tolerance of ambiguity, ICU providers, healthcare providers